Understanding inclusive entrepreneurship:With special reference to women immigrants in Arctic Finland - Yeasmin, Nafisa; Hasanat, Waliul (Finnish Yearbook of Population Research, 2022)
A recent OECD report recognises that the limited scope for immigrant women to integrate into mainstream Finnish society has kept them out of the labour market. In fact, a woman with migrant background faces several challenges to get access to the Finnish labour force and this has prompted them to become self-employed in small business, particularly in the northern part of Finland. However, establishing a small business and its operation induces diverse problems in this remote, mainly rural region. An inclusive entrepreneurship policy may support improving their condition in entrepreneurship. The study explores the main factors hindering the financial and socio-cultural inclusion of women immigrants in Northern Finland. A thematic analysis of cultural and economic inclusivity, based on descriptive phenomenology, helps understand and reconstruct a policy of inclusive societies in the context of rural entrepreneurship.